Hainan free trade port development. - An, Bo (Metro Manila, Philippines Asian Development Bank, 2019)
Hainan is also one of the designated special economic zones and free trade zones driving economic growth and reforms in the Peoples Republic of China. Recommendations in this brief call for integrated institutional policies, operational measures, and development plans to ensure that the Hainan Free Trade Port provides an enabling environment for local and foreign investments in various sectors.
Keywords: Economics; Finance -- Central Asia; Electronic books